Randomization is essential for progress in transplant medicine. - Baigent, C; Emberson, JR (2008)
Improvements in immunosuppressive regimens are likely to be moderate in size. Therefore, studies to detect them reliably require a guarantee of small biases (so randomization is essential) and small random errors. Even after adjustment, nonrandomized studies may have large biases, so are not a suitable alternative to large randomized trials.